Predominant Sources of Pharmacists’ Drug Information, and Identification of Drug Information Needs from Pharmacists in Community and Hospital Settings - Iheanacho, Chinonyerem Ogadi; U. Odili, Valentine; Oluigbo, Kennedy Emeka (Journal of Pharmacy Practice and Community Medicine)
Background: A major way to achieve improved drug therapy is through effective practice of Drug Information Services (DIS) by pharmacists. Aim: The study assessed the drug information needs from community and hospital pharmacists and their predominant sources of drug information in a Nigerian City. Methods: Cross-sectional survey involving cluster and convenience sampling methods was used to recruit hospital and community pharmacists respectively, and structured questionnaires were self-administered to them. Data was analyzed using SPSS version 21 (p≤0.05). Results: A total of 102 pharmacists participated in the study and majority 60 (58.8%), had received training on DIS. Reference books (4.58 ± 0.59) and internet (4.44 ± 0.62) respectively, were most consulted sources of drug information for community pharmacists. Similarly, reference books (4.42 ± 0.54) and the internet (4.42 ± 0.55) were also most consulted by hospital pharmacists respectively. Consultation of drug bulletins was significantly higher in hospital pharmacists than community pharmacists (p=0.006). Most frequently demanded drug information were drug cost (4.63 ± 0.52) from community pharmacists and drug dosage (4.61±0.49) from hospital pharmacists. Drug information on pharmacokinetics was significantly more frequently required from the hospital pharmacists than the community Pharmacists (p=0.002). Conclusion: Most frequently consulted literature sources among the study participants were the reference books and internet. Drug information most frequently required from community and hospital pharmacists were cost of drugs and drug dosage respectively. This emphasizes the recognized role of pharmacists in DIS, which suggests the need for regular up-to-date DI skills.
Keywords: Drug Information Services; Community Pharmacists; Hospital Pharmacists; Practice; Nigeria.